Integrasi Nilai-Nilai Islam dalam Pembelajaran Maharah Kalam Bahasa Arab di Perguruan Tinggi Keagamaan Islam - Ahimsa Ikhlasul Amal; Sa’ad Abdul Hakim; Ahmad Nur Mizan (Medan Resource Center, 2026)
This study aims to describe the integration of Islamic values in Arabic maharah kalam learning at Islamic Higher Education Institutions (PTKI), including its forms, implementation patterns, and characteristics. This qualitative descriptive study was conducted at the Arabic Education Study Program, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Raden Intan Lampung. The research involved 3 lecturers and 25 students as research subjects. Data were collected through observation, interviews, and documentation of learning activities and academic documents. The novelty of this study lies in its comprehensive analysis of the integration of Islamic values in maharah kalam learning through both explicit and implicit approaches within the context of higher Islamic education. The findings revealed that Islamic values were integrated through lesson planning, dialogue materials, speaking practices, Islamic expressions, and classroom interactions. The integrated values included aqidah, ibadah, and akhlak, with akhlak emerging as the most dominant aspect. The integration was implemented explicitly through direct explanations, prayers, and value-oriented learning materials, and implicitly through communication habits and contextual themes. The study concludes that integrating Islamic values supports students’ Arabic speaking skills while strengthening their Islamic character. Furthermore, the findings provide practical implications for the development of Arabic language learning models that are value-based, character-oriented, and aligned with Islamic educational objectives in higher education institutions.